ARE SYMPTOM FEATURES OF DEPRESSION DURING PREGNANCY, THE POSTPARTUM PERIOD AND OUTSIDE THE PERIPARTUM PERIOD DISTINCT? RESULTS FROM A NATIONALLY REPRESENTATIVE SAMPLE USING ITEM RESPONSE THEORY (IRT). Issue 2 (25th November 2014) - Hoertel, Nicolas; López, Saioa; Peyre, Hugo; Wall, Melanie M.; González‐Pinto, Ana; Limosin, Frédéric; Blanco, Carlos
<x xml:space="preserve">Abstract</x> Background Whether there are systematic differences in depression symptom expression during pregnancy, the postpartum period and outside these periods (i.e., outside the peripartum period) remains debated. The aim of this study was to use methods based on item response theory (IRT) to examine, after equating for depression severity, differences in the likelihood of reporting DSM‐IV symptoms of major depressive episode (MDE) in women of childbearing age (i.e., aged 18–50) during pregnancy, the postpartum period and outside the peripartum period. Methods We conducted these analyses using a large, nationally representative sample of women of childbearing age from the United States (n = 11, 256) who participated in the second wave of the National Epidemiologic Survey on Alcohol and Related Conditions (NESARC). Results The overall 12‐month prevalence of all depressive criteria (except for worthlessness/guilt) was significantly lower in pregnant women than in women of childbearing age outside the peripartum period, whereas the prevalence of all symptoms (except for "psychomotor symptoms") was not significantly different between the postpartum and the nonperipartum group. There were no clinically significant differences in the endorsement rates of symptoms of MDE by pregnancy status when equating for levels of depression severity. Conclusions This study suggests that the clinical presentation of depressive symptoms in women of childbearing age does not differ during pregnancy, the postpartum period and outside the peripartum period. These findings do not provide psychometric support for the inclusion of the peripartum onset specifier for major depressive disorder in the DSM‐5.